Effects of Swift-Particle Irradiations on Critical Current Density in CaKFe4As4. (September 2019) - Takahashi, A; Pyon, S; Okayasu, S; Ishida, S; Iyo, A; Eisaki, H; Imai, M; Abe, H; Terashima, T; Tamegai, T
Abstract: Introduction of columnar defects to superconductors through swift-particle irradiation enhances their critical current density ( J c ). Iron-based superconductors (IBSs) have been investigated as promising materials for practical applications because of their large J c at high magnetic fields and temperatures. Recently, another promising IBS CaKFe4 As4 (1144-type IBS) was found, and attracts much interest due to its high J c in the pristine sample. We compare effects of 800 MeV Xe, 3 MeV proton, and 320 MeV Au irradiations on the critical temperature ( T c ) and J c of CaKFe4 As4 single crystals, and compare them with irradiation effects in Ba0.6 K0.4 Fe2 As2 .